2023
DOI: 10.3390/ijms241713473
|View full text |Cite
|
Sign up to set email alerts
|

Refolding Increases the Chaperone-like Activity of αH-Crystallin and Reduces Its Hydrodynamic Diameter to That of α-Crystallin

Konstantin O. Muranov,
Nicolay B. Poliansky,
Vera A. Borzova
et al.

Abstract: αH-Crystallin, a high molecular weight form of α-crystallin, is one of the major proteins in the lens nucleus. This high molecular weight aggregate (HMWA) plays an important role in the pathogenesis of cataracts. We have shown that the chaperone-like activity of HMWA is 40% of that of α-crystallin from the lens cortex. Refolding with urea significantly increased—up to 260%—the chaperone-like activity of α-crystallin and slightly reduced its hydrodynamic diameter (Dh). HMWA refolding resulted in an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Concurrently, other methods for structural determination, such as X-ray crystallography, nuclear magnetic resonance (NMR), and infrared broad spectrum, along with biochemical assays, also provide a robust and complementary boost to the characterization and understanding of macromolecular dynamics and interactions [12,13]. Si-Bo Chen et al 2023 [12] revealed that a novel bacterial dipeptidyl peptidase III (CoDPP III) exists in a dimeric and closed conformation in the absence of a ligand and accumulates peptides and amino acids to serve as an A-signal, as evidenced by biochemical characterization and crystallization.…”
Section: Molecular Insights Intomentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, other methods for structural determination, such as X-ray crystallography, nuclear magnetic resonance (NMR), and infrared broad spectrum, along with biochemical assays, also provide a robust and complementary boost to the characterization and understanding of macromolecular dynamics and interactions [12,13]. Si-Bo Chen et al 2023 [12] revealed that a novel bacterial dipeptidyl peptidase III (CoDPP III) exists in a dimeric and closed conformation in the absence of a ligand and accumulates peptides and amino acids to serve as an A-signal, as evidenced by biochemical characterization and crystallization.…”
Section: Molecular Insights Intomentioning
confidence: 99%
“…Si-Bo Chen et al 2023 [12] revealed that a novel bacterial dipeptidyl peptidase III (CoDPP III) exists in a dimeric and closed conformation in the absence of a ligand and accumulates peptides and amino acids to serve as an A-signal, as evidenced by biochemical characterization and crystallization. Konstantin O. Muranov et al 2023 [13] experimentally determined that α-crystallin exhibits higher molecular chaperone activity than αH-crystallin. Moreover, the refolding of αH-crystallin corrects misfolding and enhances its molecular chaperone activity, offering meaningful prospects for drug development for cataracts.…”
Section: Molecular Insights Intomentioning
confidence: 99%